Hypertension in aortic coarctation - Ye, Luisa; Castaldi, Biagio; Cattapan, Irene; Pozza, Alice; Fumanelli, Jennifer; Di Salvo, Giovanni (Frontiers in Cardiovascular Medicine, 2025)
Aortic coarctation (AoC) is a common congenital heart defect, affecting 5%–8% of patients with structural congenital anomalies. Despite advances in surgical and percutaneous interventions, hypertension remains a significant complication in AoC patients, even after successful repair. Chronic hypertension develops in 20%–70% of patients and is a leading cause of long-term cardiovascular morbidity. In these patients, hypertension is associated to renin-angiotensin system activation, residual aortic arch abnormalities, and impaired aortic elasticity. Additionally, exercise-induced hypertension and masked hypertension contribute to adverse outcomes. Management of hypertension in AoC patients requires both perioperative and long-term care. Early after correction, intravenous antihypertensive agents, such as sodium nitroprusside, esmolol, and labetalol, are commonly used to stabilize blood pressure and reduce the risk of complications like cerebral hemorrhage. Oral beta-blockers, ACE inhibitors (ACE-Is), angiotensin receptor blockers (ARBs) and calcium channel blockers (CCBs) are most commonly used for chronic hypertension. In this review, we discussed about diagnostic workup and therapeutical strategies for hypertension in AoC patients.